Analytical Review of the Impact of Martial Law on the Adaptation of English Terminology in Ukraine - Tarasova, Vitalina; Miroshnychenko, Iryna; Shestakova, Svitlana; Chukhno, Tetiana; Maksymova, Anna (Translation Studies: Theory and Practice, 2025)
Martial Law in Ukraine, initiated due to Russia’s large-scale invasion in 2022, has significantly impacted various aspects of the country’s life, including linguistic processes. In globalisation and active collaboration with international organisations, English is crucial in professional communication, particularly in defense, medical, technical and humanitarian fields. This study aims to review the impact of martial law on the adaptation of English terminology in Ukraine. The methods included structured interviews with students studying English and practising translation, surveys to collect quantitative data on challenges encountered while adapting English military terminology (the study focuses on military texts originating from the United States and the United Kingdom) into Ukrainian and observations of educational sessions. A total of 43 academic works were selected to explore the article’s topic, conduct a comparative educational analysis and delve into translation processes and neology issues. The study involved 45 participants, including 15 students. The results revealed that incorporating English military terminology into Ukrainian has significantly accelerated and acquired new characteristics. The analysis of relevant literature uncovered the peculiarities of translating military terminology from diachronic and synchronic perspectives. The research findings have shown that English military terminology presents significant challenges and complexities in translation, as it serves both an expressive and a referential function. The exotic nature of these borrowed terms indicates connotative intensification, reflecting an ideologically rather than terminologically driven segmentation of extralinguistic reality.